PERAN HUKUM DALAM MENYEIMBANGKAN PERSAINGAN USAHA DI EKOSISTEM DIGITAL - Ramdin; Zuhrah (An Nuqud Journal of Islamic Economics, 2024)
The rapidly evolving digital ecosystem has created new challenges in the world of business competition, especially in relation to monopolies and market dominance by large platforms. Anti-competitive practices such as predatory pricing, data hoarding, and the use of algorithms to regulate the market further exacerbate competitive inequality. This research aims to analyse the role of law in balancing business competition in the digital era, focusing on the regulations needed to ensure fair competition in the digital ecosystem. Using a qualitative approach with a descriptive analysis method, this research examines competition regulations implemented in various countries, as well as the challenges faced in their implementation in the digital market. Data was obtained through literature study and comparison of regulations between the European Union, the United States, and Indonesia. The research findings show that while regulations such as the Digital Markets Act (DMA) in the European Union and the Antimonopoly Law in Indonesia have provided a legal basis for regulating competition, there are still gaps in addressing the dominance of digital platforms that hinder fair competition. Therefore, this study suggests the need for improvements in regulation that are more adaptive to digital dynamics, emphasising the importance of transparency, non-discrimination and sustainability principles to create a fairer market. This research provides important insights for policy development that can strengthen competition in the digital ecosystem.